SERVICE QUALITY OF THE UNIVERSITY LIBRARY TECHNICAL IMPLEMENTATION UNIT LAMBUNG MANGKURAT BANJARMASIN - Fahruraji Fahruraji; Asmu'i Asmu'i; Bachruddin Ali Akhmad; Muhammad Riduansyah Syafari (stiatabalong.ac.id, 2022)
This research is counducted in order to analyce and to give a description about the service Quality of the University Library Technical Implementation Unit Lambung Mangkurat Banjarmasin and the understand any obstacle which interferes the Service Quality of the University Library Technical Implementation Unit Lambung Mangkurat Banjarmasin Qualitative approach is used with qualitative descriptive research type. The informan selected were the library student. The data used in this research were the primary data directly gained from the informan and the secondary data were gained indirectly. The technique of collected the data was done by the interviews, observation and documentation. The collected data will be described and analyzed by a descriptive analysis technique which give the description about the University Library Technical Implementation Unit Lambung Mangkurat Banjarmasin. The result of the research showed that the University Library Technical Implementation Unit Lambung Mangkurat Banjarmasin can be said to be in acceptably good quality. This result can be seen from the indicatiors: Tangibles, Reliability, Responsiveness, Assurance and Empathy. The obstacles. found in this research were lack of book collection provided in the library the lack of facilties, the lack of human resources and the lack budget limitations. This research recommends to the University Library Technical Implementation Unit Lambung Mangkurat Banjarmasin expected to hold a collection of books, facilities and infrastructure facilities, add library technical staff, carry out budget priority scales. Keywords: Services, Service Quality